THE EFFECT OF WIDE SWADDLING ON ALPHA HIP ANGLE IN NEWBORNS AND INFANTS - Komnenovikj, Marina; Bozhinovski, Zoran; Georgieva, Daniela; Shabani, Ilir; Bogojevska Doksevska, Milena; Damjanovikj, Dejan; Atanasovski, Igor (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2025)
Developmental dysplasia of the hip (DDH) is one of the most common diseases of the musculoskeletal system. Hip dysplasia occurs in 1:100, which means that it is 10 times more common than hip dislocation. The position of flexion and abduction in newborns and infants is the most common recommendation to improve hip development. The aim of this research is to evaluate the effects of wide swaddling, i.e., to determine whether wide swaddling influences hip maturation in the first months after birth and whether it has an effect on increasing the alpha angle of the hip during ultrasound examination. Materials and methods: A prospective, clinical, stratified study was conducted on male and female newborns and infants with type Ia, Ib and IIa hip according to the Graf method. The subjects were divided into two groups. The first group included 20 newborns and infants using wide swaddling (40 hips monitored). The second group consisted of 23 newborns and infants who were not swaddled (46 hips monitored). The wide swaddling method involved using an additional cloth diaper and one wide swaddle diaper. Subjects underwent hip ultrasound according to the Graf method during the first hip examination at 4–8 weeks of age, and again two months after the initial assessment. Results: a simple procedure such as wide swaddling influences an increase in the alpha angle of the hip. There is an effect on hip development with faster transition from type IIa to type I according to the Graf method. After two months, the progression of hip maturation in the swaddling group was evident, while hips in the non-swaddling group remained type I and II, indicating that there is also a normal maturation in the other group. Further research is necessary to evaluate the long-term effects of wide swaddling on hip development.
Keywords: developmental hip dysplasia; sonography; Graf; prevention; wide swaddling